2022
DOI: 10.1186/s12974-022-02632-6
|View full text |Cite|
|
Sign up to set email alerts
|

Motor neuron survival is associated with reduced neuroinflammation and increased autophagy after brachial plexus avulsion injury in aldose reductase-deficient mice

Abstract: Brachial plexus root avulsion (BPRA) is frequently caused by high-energy trauma including traffic accident and birth trauma, which will induces massive motoneurons (MNs) death as well as loss of motor and sensory function in the upper limb. The death of MNs is attributed to energy deficiency, neuroinflammation and oxidative stress at the injured ventral horn of spinal cord triggered by BPRA injury. It has been reported which aldose reductase (AR), an endogenous enzyme that catalyzes fructose synthesis, positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Autophagy, an intracellular self-degradation system, is an essential biological process that removes unnecessary cytosol, cytoplasmic organelles, and even microbes from cells [ 10 12 ]. Recent studies have revealed that autophagy in macrophages sequesters pro-inflammatory mediators, and it is therefore being recognized as a crucial process involved in regulating inflammation in various diseases, including atherosclerosis [ 13 , 14 ], inflammatory bowel disease [ 15 ], uveitis [ 16 ], infection [ 17 19 ], peripheral neuronal injury [ 20 ], and brain ischemia [ 21 ]. Considering that macrophages are key cells in the generation and resolution of inflammatory pain [ 1 , 22 , 23 ], autophagy in macrophages can be expected to play pivotal roles in postoperative pain and inflammation as well as their resolution, and is therefore a potential therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy, an intracellular self-degradation system, is an essential biological process that removes unnecessary cytosol, cytoplasmic organelles, and even microbes from cells [ 10 12 ]. Recent studies have revealed that autophagy in macrophages sequesters pro-inflammatory mediators, and it is therefore being recognized as a crucial process involved in regulating inflammation in various diseases, including atherosclerosis [ 13 , 14 ], inflammatory bowel disease [ 15 ], uveitis [ 16 ], infection [ 17 19 ], peripheral neuronal injury [ 20 ], and brain ischemia [ 21 ]. Considering that macrophages are key cells in the generation and resolution of inflammatory pain [ 1 , 22 , 23 ], autophagy in macrophages can be expected to play pivotal roles in postoperative pain and inflammation as well as their resolution, and is therefore a potential therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…For that, the establishment of animal models of root avulsion allowed the advance in understanding the several reactions to proximal axotomy as well as aspects of the regeneration process [4][5][6][7][8][9][10][11]. Thus, ventral root avulsion (VRA) in rats has become an animal model widely used since it can recapitulate both acute and chronic phases following injury [3,[12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified that the article note about co-first author and equal contribution were missing.…”
mentioning
confidence: 99%